Discovering the Synthesis between Marxism and Xi Jinping’s thought on Socialism with Chinese Characteristics for a New Era - V. V. Sukhomlinova (Концепт: философия, религия, культура, 2020)
It remains highly relevant to analyze international relations with a special emphasis not only on the political, but also on the cultural dimension of the «East-West» dichotomy. If we need to maintain control over the process of intercultural communication, it needs to be reconsidered from a philosophical standpoint. In this case what is crucial is to further deepen our understanding of China and its ability to create synthetic political and economic doctrine. This article investigates the mechanism of self-reproduction of Chinese ideology. The author names it «borrow-and-interpret». During the era of Chinese empire this mechanism was applied to Confucianism when it was attacked by opposing philosophical teachings (like legalism, Taoism, Buddhism and western liberalism) threatening to undermine the Confucian-based political regime. Sinceearly Confucian texts were highly condensed in meaning, it offered Confucian bureaucracy to interpret them in various ways. They borrowed some relevant thoughts and concepts from other philosophical doctrines and integrated them into the commentaries of Confucian thought. Confucianism therefore always remained up-to-date and nominally coherent. Today China’s President Xi Jinping, along with his predecessors, tries to make Marxism more relevant to Chinese day-to-day practice. It is now Marxism that is updated through applying «borrow-and-interpret» mechanism to it. Xi Jinping merges core socialist values with Confucian ethical maxims. In doing so he hopes to eliminate the negative influence of western values on Chinese society and further consolidate the power of CPC.